An old drug with a new future: bendamustine in multiple myeloma. (November 2013) - Gentile, Massimo; Recchia, Anna Grazia; Mazzone, Carla; Vigna, Ernesto; Martino, Massimo; Morabito, Lucio; Lucia, Eugenio; Bossio, Sabrina; De Stefano, Laura; Granata, Teresa; Palummo, Angela; Morabito, Fortunato
Abstract : Introduction: Bendamustine is a unique bifunctional alkylating agent with promising activity in multiple myeloma (MM). It is currently licensed in Europe for use as frontline treatment with prednisolone for patients with MM who are unsuitable for transplantation and who are contraindicated for thalidomide and bortezomib therapy. Areas covered: Studies evaluating the safety and efficacy of bendamustine administered alone or in combination in both the upfront and relapse settings of MM patients, including those with renal insufficiency, were reviewed. The use of bendamustine as conditioning for autologous stem-cell transplantation and the possibility of stem-cell mobilization after bendamustine therapy are discussed. Expert opinion: Bendamustine seems to be efficacious either in monotherapy or in combination with other drugs in previously treated or untreated patients. This is due to its unique mechanism of action including its ability to activate apoptosis and inhibit mitotic checkpoints, making it potentially more effective than other alkylating agents. Moreover, it has an acceptable toxicity profile and is suitable for patients with renal impairment. Finally, this drug does not seem to compromise the possibility of achieving a stem-cell mobilization. Nonetheless, data from Phase III studies demonstrating its effectiveness in terms of overall survival are not yet available.